An unusual cause of optic neuritis: rickettsiosis disease - Loukil Hanen; Snoussi Mouna; Frikha Faten; Ben Salah Raida; Jallouli Moez; Chérif Yosra; El Aoud Sahar; Marzouk Sameh; Bahloul Zouhir (Asian Pacific Journal of Tropical Biomedicine, 2014)
Optic neuritis (ON) may be associated to a range of autoimmune or infectious diseases. We report herein a case of ON induced by Rickettsia conorii. A 53-year-old woman presented with a recent decrease in visual acuity and headache. ON was diagnosed on the basis of ophthalmologic examination and flash visual evoked potentials. Etiological investigation made in our department eliminated first autoimmune disorders (vasculitis and connective tissue diseases). Rickettsial optic neuritis was confirmed by detection of specific antibodies in serum and the negativity of other serologic tests. An association between corticosteroids and cyclines was prescribed with improvement of visual acuity.